The Function of Honorific Term Ité: Cultural Perspectives from Manggarai, Indonesia - Menggo, Sebastianus (Universitas Sanata Dharma, 2024)
Culture pertains to human existence and encompasses the various aspects of a civilization’s way of life. On the other hand, language refers to the complex communication system employed by individuals inside a specific culture or group. Language utilization typically represents the societal customs, cognitive processes, cognitive functioning, historical context, and interconnections within a given human civilization. Utilizing the inclusive personal pronoun